PARENTAL TIME INVESTMENT AND INTERGENERATIONAL MOBILITY - Minchul Yum (International Economic Review, 2022)
This article constructs an overlapping generations general equilibrium model to explore the extent to which heterogeneity in time investment shapes intergenerational mobility of lifetime income. The calibrated model successfully accounts for untargeted distributional aspects of income mobility. Counterfactual exercises show that removing heterogeneity in parental time investment reduces intergenerational persistence by around 7–8% for early childhood but only marginally in later childhood. Policy experiments find that an asset-tested subsidy for parental monetary investments in early childhood can raise intergenerational mobility in a cost-effective way, though it reduces mobility substantially if given to parents with older school-aged~children.
Keywords: 330